The Effect of PjBL Assisted By Written Feedback Assessment on Students' High-Level Thinking Abilities in Ecosystem Material - Ayuni, Fuji Nur; Ratnasari, Jujun; Juhanda, Aa (Jurnal Report of Biological Education, 2025)
Background: This study is behind the difficulties of students in working on HOTS, so this study aims to find out the effect of project based learning assisted by assessment written feedback on students' high-level thinking ability on ecosystem material. Methods: The method used is a method of pseudo-experimentation with a non-equivalent control group design. The subject of the study was a grade X MAN 1 student in Sukabumi City. The sampling technique using purposive sampling was 60 students, 30 in experimental class and 30 in control class. The instruments used are about high-level thinking ability tests and the response of students of Project Based Learning models to high-level thinking ability. Results: The research results stated that the pretest-posttest value with N-Gain calculations of 0.64 is in the medium category with the average pretest-posttest value difference of 83.23. N-gain results based on high level thinking ability indicators of 0.72 or in high category. the average student response rate in the use of project based learning models to high-level thinking abilities is 83 or in excellent categories. Conclusion: The conclusion of this study is the use of project based learning models assisted by assessment written feedback affects students' high-level thinking abilities.